Foetal haemodynamic response to anaemia - Thammavong, Keooudone (ESC Heart Fail, 2020)
This study aims to update new knowledge regarding foetal cardiovascular response to anaemia, using foetal haemoglobin Bart's disease as a study model. Original research articles, review articles, and guidelines were narratively reviewed and comprehensively validated. The main foetal cardiovascular changes in response to anaemia are consequences of hypervolaemia and increased cardiac output to meet tissue oxygen requirement. New challenging insights are as follows: (i) the earliest morphological change is an increase in cardiac size and remodelling of the sphericity (an increase in diameter more pronounced than that in long axis) followed by several markers, such as placentomegaly and hepatosplenomegaly. (ii) The earliest functional change is increased peak systolic velocity of the red blood cells because of low viscosity, especially in the middle cerebral artery. (iii) The foetal heart has very high reserve potentials to cope with anaemia: increasing workload without increased central venous pressure and increased myocardial performance without compromising shortening fraction. This hard‐working period with good performance lasts long, including most part of the second and third trimester. (iv) At the time cardiomegaly myocardial cellular damage has already occurred, in spite of good cardiac function. (v) Anaemic hydrops foetalis is mainly due to hypervolaemia, hypoalbuminaemia, and high vascular permeability, not heart failure. (vi) Foetal heart failure occurs only when the adaptive mechanism becomes exhausted or long after the development of anaemic hydrops foetalis. Heart failure is a very late result of a longstanding overworked heart. (vii) Ultrasound is highly effective in the detection of foetal response to anaemia. An increase in cardiac size and middle cerebral artery is very helpful in predicting the affected foetuses in pre‐hydropic phase. (viii) Theoretically, intrauterine treatment of anaemic hydrops results in satisfactory outcomes as long as cardiac function is normal, but intrauterine intervention should be strongly considered in pre‐hydropic phase because myocardial cell damage could have already occurred in this phase or early hydropic phase. Anaemic hydrops foetalis is not primarily caused by heart failure as commonly advocated, but it is rather a consequence of hypervolaemia, hypoalbuminaemia, and high vascular permeability while heart failure is a very late consequence of a longstanding overworked heart. New insights gained from this review may be useful to base clinical practice on which sonographic markers imply significant pathological changes, how ultrasound can be helpful in early detection of anaemic response, when intrauterine transfusion for anaemia due to non‐lethal causes should be administered, etc.